Nucleotide sequence alignment of hdcA from Gram-positive bacteria - Diaz, Maria (Data Brief, 2016)
The decarboxylation of histidine -carried out mainly by some gram-positive bacteria- yields the toxic dietary biogenic amine histamine (Ladero et al. 2010 〈10.2174/157340110791233256〉 [1], Linares et al. 2016 〈http://dx.doi.org/10.1016/j.foodchem.2015.11.013〉〉 [2]). The reaction is catalyzed by a pyruvoyl-dependent histidine decarboxylase (Linares et al. 2011 〈10.1080/10408398.2011.582813〉 [3]), which is encoded by the gene hdcA. In order to locate conserved regions in the hdcA gene of Gram-positive bacteria, this article provides a nucleotide sequence alignment of all the hdcA sequences from Gram-positive bacteria present in databases. For further utility and discussion, see 〈http://dx.doi.org/ 10.1016/j.foodcont.2015.11.035〉〉 [4].